PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. TRI MITRA SEJAHTERA PEKANBARU - Aznuriyandi, Aznuriyandi (Jurnal Tepak Manajemen Bisnis, 2016)
This research was conducted at PT. Prosperous Trimitra Pekanbaru. The purpose of thisstudy is Knowing Effect of Motivation and Leadership on Employee Performance PT. Tri MitraSejahtera Pekanbaru. While the benefits of this research is as a material consideration in applyingMotivation and Leadership Award for improving employee performance PT. Tri Mitra SejahteraPekanbaru in the future. The study used primary data obtained from questionnaires and interviews, andthe sampling method used is random sampling by the formula Slovin. Where the amount of the overallpopulation as many as 74 people. For this study the entire population sampled, so that the samplingmethod using census method. The data an8alysis used is multiple linear regression analysis. From theresults of research on the influence of discipline in improving the performance of employees of PT. TriMitra Sejahtera Pekanbaru with a coefficient of determination (R square), the amount is 0.315 That is31.5% while the remaining 68.5% is influenced by other variables not examined in this study.